Nauka i metafizyka (I) - Zawirski, Zygmunt (Filozofia Nauki, 1995)
The text is the first part of an unpublished manuscript, written in 1920. According to the author, on the one hand, it is impossible to create metaphysics based on experience, and giving absolutely safe interpretation of the reality. But, on the other hand, experiential metaphysics, being satisfied with only probable results, is not of exactly scientific character. Nevertheless, we should work at constructing a „metaphysics”, integrating results of particular sciences into one system, free of contradiction, but being conscious of provisionality of its theses. The main variable for such a „metaphysics” should always be „physical world”.